New variables and new agreements between 10 Hz global positioning system devices in tennis drills - Gale-Ansodi, C.; Langarika-Rocafort, A.; Usabiaga, O.; Castellano Paulis, J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2016)
The knowledge about physical demands in different sports has increased, thanks to the application of global positioning system devices. The reliability and validity of 10 Hz global positioning system devices have been assessed by some authors. The majority of the studies only addressed the reliability of the devices or, in other words, the ability of scores of global positioning system device to differentiate among subjects or objects. The reliability is based on correlations (such as the intraclass correlation coefficient) which do not give the researcher information that can be interpreted in a practical way. In this way, the aim of this study was to assess the grade of agreement among repeated measurements made on the same subject using two global positioning system devices simultaneously. Four trained male tennis players participated in the study. The participants completed tennis-simulated point-games (n = 32), each player wearing two devices at the same time. Global indicators, such as Player Load (PL), Exertion Index (EI) and Equivalent Distance Index (EDI) per minute, were monitored through the use of global positioning system devices (MinimaxX v4.0; Catapult Innovations, Melbourne, Australia) operating at the above-mentioned sampling frequency of 10 Hz. The systematic error is that there is tendency of the global positioning system devices to measure systematically different from others Vmean (-1.03 m · min-1), Vpeak (-10.31 m · min-1), Equivalent Distance Index (0.63 ratio), PLmin (0.35 UA min-1) and EImin (-0.01) variables. As for random error (limit of agreement), we would expect that in PLmin, the global positioning systems would differ in 95% of the cases between 2.12 and -1.42 m · min-1; any value out of the limits of agreement would result relevant for the practical point of view. We concluded that the global positioning system devices produce systematically different results from one another; therefore, the bias from one global positioning system to another should be subtracted to compare the results between the global positioning systems.